TINJAUAN YURIDIS TERHADAP PERBUATAN DEBITUR YANG MENGALIHKAN ATAU MENJUAL BENDA JAMINAN FIDUSIA DAN AKIBAT HUKUMNYA - Arif Fakrur Rozi (Universitas 17 Agustus 1945 Samarinda, 2017)
ABSTRACT Regarding the act of the debtor transferring or selling the object of fiduciary guarantee is obviously not legally granted, since the object of the collateral object is the safeguarding, if there is any sale of fiduciary object by debtor, this is a criminal act of embezzlement as threatened and governed by Article 372 of the Criminal Code . The object of fiduciary assurance object is seen from its legal aspect as security in fiduciary agreement. Based on Article 15 Paragraph (3) of Law no. 42 of 1999 on Fiduciary states that if the debtor breaches the pledge, the fiduciary receiver has the right to sell the object which is the object of fiduciary guarantee on his own power. So here it is explicit that the debtor is not allowed to sell or transfer the object of the collateral as this is a safeguard in the fiduciary agreement. Implementation of the consumer financing agreement with fiduciary guarantee, the consumer takes the action causing the financing company to suffer a loss and of course the act disturbs the implementation of the agreed agreement. The act is to misuse the fiduciary asset by transferring the fiduciary assurance object without the knowledge and permission of the pebiayaan company, whereas the proof of ownership of the vehicle is still controlled by the finance company. Violation of this provision may be imposed by Article 372 of the Criminal Code in conjunction with Article 23 paragraph (2) jo Article 36 of Law no. 42 of 1999 on Fiduciary Guarantee. If the consumer infringes then the consumer within 3month must submit the vehicle or the consumer must give the right of substance to FINANCE COMPANY to make withdrawal.